ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS TERHADAP PENGEMBALIAN INVESTASI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Dolok Saribu, Winda Sari; E Janrosl, Viola Syukrina (SCIENTIA JOURNAL, 2021)
This study aims to analyze the profitability and liquidity of the investment returns of companies listed on the Indonesia Stock Exchange. The benchmark of each factor is the return on equity as the proportion of profitability, the current ratio as the proportion of liquidity and the proportion of dividends payout ratio as the proportion of return on investment. The exploration technique uses a quantitative strategy by utilizing the fiscal reports of organizations listed on the Indonesia Stock Exchange. The population is the food and beverage producing sub-sector which is listed on the Indonesia Stock Exchange as many as 32 companies. The examination method in this study used purposive sampling. The sample used is 10 companies listed on the Indonesia Stock Exchange in the period 2016 - 2020 with 50 company data obtained. The data test methods used are normality test, multicollinearity, heteroscedasticity, autocorrelation and using multiple linear analysis consisting of t-test and f-test and coefficient of determination test using SPSS variance 25. Based on the results of profitability testing it affects investment returns and variables liquidity affects the return on investment. Simultaneously, productivity and liquidity significantly affect the return on investment. Keywords:Profitability; Liquidity; Return On Investment